The Influence of Learning Motivation and Family Environment on Student Independence Mediated by Learning Discipline among Students at SPK School Surabaya - Dewa Made Dwikamayuda; Ida Ayu Nyoman Maye Denia Ari; Ni Ekawati (IAHN-TP Palangka Raya, 2024)
The purpose of this study is to examine and explain the influence of learning motivation and family environment on student independence, mediated by student discipline. This research is quantitative in nature. The population of the study consists of all elementary school students at SPK Surabaya for the 2023/2024 academic year. The sampling technique used is census sampling (saturated sampling), where the entire population is used as the research sample, totaling 121 individuals. Data collection was conducted using questionnaires. The data analysis method employed in this study is descriptive and inferential statistical analysis, specifically using the SEM-PLS analysis technique. The results indicate that learning motivation has a positive and significant effect on independence with a path coefficient of 0.245 and a P-value of 0.005. The family environment has a positive and significant effect on independence with a path coefficient of 0.194 and a P-value of 0.026. Learning motivation has a positive and significant effect on discipline with a path coefficient of 0.504 and a P-value of 0.000. The family environment has a positive and significant effect on discipline with a path coefficient of 0.203 and a P-value of 0.014. Discipline has a positive and significant effect on independence with a path coefficient of 0.502 and a P-value of 0.000. Discipline mediates the relationship between learning motivation and independence with a VAF value of 0.508. Discipline also mediates the relationship between family environment and independence with a VAF value of 0.344.